2020
DOI: 10.1016/j.adro.2019.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Results From a Phase II Study on Image Guided, Intensity Modulated Radiation Therapy With Simultaneous Integrated Boost in High-Risk Prostate Cancer

Abstract: There is no consensus on how to treat high-risk prostate cancer, and long-term results from hypofractionated radiation therapy are lacking. We report 10-year results after image guided, intensity modulated radiation therapy with hypofractionated simultaneous integrated boost and elective pelvic field. Methods and Materials: Between 2007 and 2009, 97 consecutive patients with high-risk prostate cancer were included, treated with 2.7 to 2.0 Gy  25 Gy to the prostate, seminal vesicles, and elective pelvic field.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 42 publications
(45 reference statements)
0
12
0
Order By: Relevance
“…A small single institution study recently reported 10-year results after image guided, intensity modulated radiation therapy with hypofractionated simultaneous integrated boost and elective pelvic fields [ 35 ]. In the 82 HR-VHR treated patients, 10-year bRFS was 64%, PCSS 90%, and OS 72%.…”
Section: Discussionmentioning
confidence: 99%
“…A small single institution study recently reported 10-year results after image guided, intensity modulated radiation therapy with hypofractionated simultaneous integrated boost and elective pelvic fields [ 35 ]. In the 82 HR-VHR treated patients, 10-year bRFS was 64%, PCSS 90%, and OS 72%.…”
Section: Discussionmentioning
confidence: 99%
“…In our clinical procedure, the patients in the present study were planned for a maximum of 60 Gy (about 62GyEDQ2) delivered to 10 cc of the rectal volume and with restrictions to the volume receiving 50 Gy 1 . This resulted in very little rectal toxicity, indirectly indicating that the obtained changes to the EUD from pCT in these patients were acceptable 25 …”
Section: Discussionmentioning
confidence: 90%
“…1 This resulted in very little rectal toxicity, indirectly indicating that the obtained changes to the EUD from pCT in these patients were acceptable. 25 Since dose accumulation across fractions is difficult, we used the dose to the IMS as a substitute for the true dose when comparing dose-volume parameters. Under the assumption that the rectum is in a dose region with a constant gradient, the dose to the IMS will be the same as the expected accumulated dose to the deforming organ.…”
Section: Discussionmentioning
confidence: 99%
“…Not until the completion of the ongoing SPCG-15 trial, randomized evidence will be available on survival outcomes in men with T3 tumors treated with RP +/− aRT compared with dose-escalated RT combined with ADT (NCT02102477). Further, even in patients with high-risk PCa, survival differences among curative treatment groups may become evident only after long-term follow-up [21] .…”
Section: Introductionmentioning
confidence: 99%